2019
DOI: 10.1063/1.5074095
|View full text |Cite
|
Sign up to set email alerts
|

Fully nonlinear simple internal waves over subcritical slopes in continuously stratified fluids: Theoretical development

Abstract: Numerical investigation of internal solitary waves of elevation type propagating on a uniform slope

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
(195 reference statements)
0
4
0
Order By: Relevance
“…When ISW undergoes dramatic changes in the seafloor during its propagation, it will cause changes in the thickness of the fluid, which in turn affects the evolution of ISW (Mashayek et al, 2017;Wang et al, 2020;Wei et al, 2012). Seafloor slope also affects energy dissipation in ISW, which in turn affects resuspension (Shimizu, 2019). The influence of bedforms and slopes on internal wave propagation has always been a research hotspot (Tian et al, 2024).…”
Section: Influence Of Seafloor On Iswmentioning
confidence: 99%
See 1 more Smart Citation
“…When ISW undergoes dramatic changes in the seafloor during its propagation, it will cause changes in the thickness of the fluid, which in turn affects the evolution of ISW (Mashayek et al, 2017;Wang et al, 2020;Wei et al, 2012). Seafloor slope also affects energy dissipation in ISW, which in turn affects resuspension (Shimizu, 2019). The influence of bedforms and slopes on internal wave propagation has always been a research hotspot (Tian et al, 2024).…”
Section: Influence Of Seafloor On Iswmentioning
confidence: 99%
“…Internal waves are thought to cause sediment resuspension, affect particle redeposition, and correlate with the distribution of bottom and middle nepheloid layers and seafloor slopes (Cacchione et al, 2002). Shimizu (2019) studied the dynamics of internal waves theoretically and found that the flat seabed is suitable for the existing internal wave theory, and the seafloor slope exceeding the critical area will increase the error. The different energy propagation modes caused by ISW passing through different seabed slopes will inevitably affect the process of suspending seabed sediments.…”
Section: Influence Of Seafloor Slope On Iswmentioning
confidence: 99%
“…The dynamics of completely nonlinear internal waves in continuously stratified fluids were studied in [9]. The study was conducted using a new theory of simple waves (or the Riemann waves) with topographic effects of the 2nd order.…”
Section: Literature Review and Problem Statementmentioning
confidence: 99%
“…doi: https:// doi.org/10.15376/biores. 9 ergy of undulatory motion which is transferred through a cross-section per unit time, that is, the energy flux, is an important characteristic. Growth or reduction of energy flux of internal waves also creates a significant impact on natural processes in water bodies.…”
Section: Introductionmentioning
confidence: 99%